Pengaruh Implementasi Kebijakan Program Kartu Indonesa Pintar terhadap Motivasi Belajar Siswa (Studi Kasus di SMPN 17 Bekasi) - Irfanudin, Irfanudin (Neolectura, 2023)
The purpose of this study was to determine the Effect s of the Implementation of the Smart Indonesia Card Policy on Student Learning Motivation at SMP Negeri 17 Bekasi. The data used in this study is primary data where the primary data data collection method is by means of a questionnaire technique (questionnaire). After the writer did the analysis and was careful, it could be seen that there was an influence between the implementation of the smart Indonesian card program policy on student learning motivation by obtaining a t-count of 2.710 and a t-table of 0.679 at a significance level which showed the level of relationship was in the low category. Meanwhile, the magnitude of the influence of the implementation of the smart card program policy on student motivation was 12%.